Cellular localization of uranium in the renal proximal tubules during acute renal uranium toxicity. Issue 12 (13th March 2015) - Homma‐Takeda, Shino; Kitahara, Keisuke; Suzuki, Kyoko; Blyth, Benjamin J.; Suya, Noriyoshi; Konishi, Teruaki; Terada, Yasuko; Shimada, Yoshiya
Abstract Renal toxicity is a hallmark of uranium exposure, with uranium accumulating specifically in the S3 segment of the proximal tubules causing tubular damage. As the distribution, concentration and dynamics of accumulated uranium at the cellular level is not well understood, here, we report on high‐resolution quantitative in situ measurements by high‐energy synchrotron radiation X‐ray fluorescence analysis in renal sections from a rat model of uranium‐induced acute renal toxicity. One day after subcutaneous administration of uranium acetate to male Wistar rats at a dose of 0.5 mg uranium kg–1 body weight, uranium concentration in the S3 segment of the proximal tubules was 64.9 ± 18.2 µg g–1, sevenfold higher than the mean renal uranium concentration (9.7 ± 2.4 µg g–1). Uranium distributed into the epithelium of the S3 segment of the proximal tubules and highly concentrated uranium (50‐fold above mean renal concentration) in micro‐regions was found near the nuclei. These uranium levels were maintained up to 8 days post‐administration, despite more rapid reductions in mean renal concentration. Two weeks after uranium administration, damaged areas were filled with regenerating tubules and morphological signs of tissue recovery, but areas of high uranium concentration (100‐fold above mean renal concentration) were still found in the epithelium of regenerating tubules. These data indicate that site‐specific accumulation of uranium in micro‐regions of the S3 segment of the proximal tubules and retention of uranium in concentrated areas during recovery are characteristics of uranium behavior in the kidney. Copyright © 2015 John Wiley & Sons, Ltd.